KAJIAN PENGOLAHAN SORBET CAMPURAN TERONG BELANDA DAN BUAH BIT SEBAGAI PRODUK PANGAN FUNGSIONAL - DIAN HASNI; SYARIFAH ROHAYA; NANDA SUPRIANA (Jurnal Sagu, 2017)
Terong belanda (Cyphomandra betacea S.) is fruit with tremendous health benefits, has aromatic flavor butless-interesting colors. On the other hand, beet root (Beta vulgaris L.) reported to have betalain pigment,which produced red-purple natural colors which potentially used as natural food coloring. Based on that,these fruits above potentially consider as raw material for frozen dessert like sorbet or ice cream in order tomaintain its nutritional values. Aims of this research are to determine and investigate the effects of proportionalratio of mixed fruits and CMC concentrations towards total acid, vitamin C and total solid as well asantioxidant activities of sorbet. Results showed that larger portion of terong belanda significantly increasedtotal acid and vitamin C, whereas CMC concentrations tend to increase total solid of produced sorbet.Sorbet from this research has vitamin C±3.14 mg/100g product, total acid ± 0.25% and total solid 18.35oBrix.